Responses of tree growth, leaf area and physiology to pavement in Ginkgo biloba and Platanus orientalis - Cui, Bowen; Wang, Xuming; Su, Yuebo; Gong, Cheng; Zhang, Danhong; Ouyang, Zhiyun; Wang, Xiaoke (Frontiers in Plant Science, 2022)
Trees growing on paved lands endure many environmental stresses in the urban environment. However, the morphological and physiological mechanisms underlying tree adaptation to pavement in the field are less known. In this study, we investigated 40 sites where Ginkgo biloba and Platanus orientalis grow on adjacent pairs of paved and vegetated plots in parks and roadsides in Beijing, China. Relative to the vegetated land, the mean increments in the diameter at breast height and height in the paved land were significantly decreased by 44.5% and 31.9% for G. biloba and 31.7% and 60.1% for P. orientalis, respectively. These decreases are related to both the decrease in assimilation products due to the reductions in leaf area, leaf total nitrogen content, and chlorophyll content and the increase in energy cost due to the synthesis of more soluble sugar and proline for mitigating stress. The increase in leaf soluble sugar content, proline content, and δ13C indicated that trees could adapt to the paved land through the regulation of osmotic balance and the enhancement of water-use efficiency. Piecewise structural equation models showed that trees growing on the paved land are stressed by compounding impacts of the leaf morphological and physiological changes. Therefore, it is critical to explore the complex response of plant morphological and physiological traits to the pavement-induced stress for improving tree health in urban greening.